Deterministic modelling of freshwater lakes and reservoirs: Current trends and recent progress. (October 2021) - Soares, Laura Melo Vieira; Calijuri, Maria do Carmo
Abstract: Deterministic models have emerged as a widely accepted tool for investigations in lentic aquatic ecosystems. In this study, an extensive literature review is provided by an inventory of papers published over the last six years (2015–2020) to explore the recent progress of deterministic models applied to lakes and reservoirs. The current trends include the application of well-established models across broad ranges of time and spatial scales; the integration of lake, catchment and climate models, in addition to multi-model ensemble approaches; and the proliferation of high-frequency sensors and the usage of remote sensing images for model initialisation, forcing data inputs, and calibration and validation. It is expected that the emerging trends in modelling lakes and reservoirs can be of great use for future research prospects as a source of information for subsequent studies in the field. Highlights: Contemporary developments: open-source models and better representation of functional groups of phytoplankton. Contemporary approaches: coupling models and multi-model ensemble. Contemporary data: high-frequency sensors and satellite remote images. Contemporary challenges: poor predictive capacity of ammonium, phosphate, and total phosphorus.